Comprehensive mapping of O‐glycosylation in flagellin from Campylobacter jejuni 11168: A multienzyme differential ion mobility mass spectrometry approach. Issue 16 (15th June 2015) - Ulasi, Gloria N.; Creese, Andrew J.; Hui, Sam Xin; Penn, Charles W.; Cooper, Helen J.; Barran, Perdita; Cooper, Helen; Eyers, Claire
<x xml:space="preserve">Abstract</x> Glycosylation of flagellin is essential for the virulence of Campylobacter jejuni, a leading cause of bacterial gastroenteritis. Here, we demonstrate comprehensive mapping of the O‐glycosylation of flagellin from Campylobacter jejuni 11168 by use of a bottom‐up proteomics approach that incorporates differential ion mobility spectrometry (also known as high field asymmetric waveform ion mobility spectrometry or FAIMS) together with proteolysis with proteinase K. Proteinase K provides complementary sequence coverage to that achieved following trypsin proteolysis. The use of FAIMS increased the number of glycopeptides identified. Novel glycans for this strain were identified (pseudaminic acid and either acetamidino pseudaminic acid or legionaminic acid), as were novel glycosylation sites: Thr208, Ser343, Ser348, Ser349, Ser395, Ser398, Ser423, Ser433, Ser436, Ser445, Ser448, Ser451, Ser452, Ser454, Ser457 and Thr465. Multiply glycosylated peptides were observed, as well as variation at individual residues in the nature of the glycan and its presence or absence. Such extreme heterogeneity in the pattern of glycosylation has not been reported previously, and suggests a novel dimension in molecular variation within a bacterial population that may be significant in persistence of the organism in its natural environment. These results demonstrate the usefulness of differential ion mobility in proteomics investigations of PTMs.